Security in an Interconnected World
X, 183 p. 27 illus., 22 illus. in color.
Keywords: This open access book follows the idea that security policy must be based on strategic analysis. Defence policy and the role of the armed forces can subsequently be determined on the grounds of said analysis. More than ever, internal and external security, and developments both in the Netherlands and abroad are interconnected. The world order is shifting, the cooperation within NATO and the EU is under pressure and the Dutch armed forces are gasping for breath. What is the task of Dutch security and the defence policy? There have been growing calls in the last few years to end the devastating cuts in the defence budget and to invest more in security. The acute threats and conflicts in which the Netherlands are involved have served as a wake-up call. The shooting down of Flight MH17 over Ukraine, the streams of refugees from Syria and other countries, the conflict with Da’esh in Syria and Iraq, and terrorist threats reveal how events in many of the world’s flash-points havea direct or indirect impact on the Netherlands. Conflicts in other countries have a spill-over effect in The Netherlands. This is illustrated by tensions between population groups and the clashes over the Gülen schools after the failed putsch in Turkey on 15 July 2016 and over the constitutional referendum in that country. How do we ensure that any additional funds are not divided amongst the branches of the armed forces without any sense of strategic direction? What should a future-proof security policy that plots the course of defence policy entail? What strategic analyses should lie behind the political choices that are made? This book answers these questions and offers a comprehensive framework addressing among other things human security, national security and flow security.